Multifunctional lignin-based nanocomposites and nanohybrids - Lizundia, Erlantz; Sipponen, Mika H; Greca, Luiz G; Balakshin, Mikhail; Tardy, Blaise L; Rojas, Orlando J; Puglia, Debora (Green chemistry : an international journal and green chemistry resource : GC, 2021)
Significant progress in lignins valorization and development of high-performance sustainable materials have been achieved in recent years. Reports related to lignin utilization indicate excellent prospects considering green chemistry, chemical engineering, energy, materials and polymer science, physical chemistry, biochemistry, among others. To fully realize such potential, one of the most promising routes involves lignin uses in nanocomposites and nanohybrid assemblies, where synergistic interactions are highly beneficial. This review first discusses the interfacial assembly of lignins with polysaccharides, proteins and other biopolymers, for instance, in the synthesis of nanocomposites. To give a wide perspective, we consider the subject of hybridization with metal and metal oxide nanoparticles, as well as uses as precursor of carbon materials and the assembly with other biobased nanoparticles, for instance to form nanohybrids. We provide cues to understand the fundamental aspects related to lignins, their self-assembly and supramolecular organization, all of which are critical in nanocomposites and nanohybrids. We highlight the possibilities of lignin in the fields of flame retardancy, food packaging, plant protection, electroactive materials, energy storage and health sciences. The most recent outcomes are evaluated given the importance of lignin extraction, within established and emerging biorefineries. We consider the benefit of lignin compared to synthetic counterparts. Bridging the gap between fundamental and application-driven research, this account offers critical insights as far as the potential of lignin as one of the frontrunners in the uptake of bioeconomy concepts and its application in value-added products.